Strategi Ketidaksantunan Bahasa dalam Kalangan Komunitas Facebook di Malaysia - Mohd. Adam Fazery Jeffry; Nor Shahila Mansor; Siti Zobidah Omar (Universitas Sebelas Maret, 2023)
This study focuses on the impoliteness strategies used in interactions among Facebook users in Malaysia. It is also scrutinized the perception of Malaysian netizens regarding the impoliteness strategies used in social media interactions. A mix of the qualitative descriptive and quantitative methods was employed. An approach of a qualitative descriptive is to comprised social interactions in the selected Facebook pages that contained the construction of impoliteness strategies. A total of 288 comments from netizens were selected, examined, and analyzed using the Impoliteness Strategies (Culpeper, 2011). The findings showed that there are various patterns of impoliteness strategies used, such as bald on record impoliteness, sarcasm, and inappropriate address forms. Whereas a quantitative approach involved a questionnaire that intended to determine the perception of netizens regarding the use of impoliteness strategies and factors that instigate the use of these strategies in social media interactions. Respondents consisted of 100 students aged between 18 to 35 years, randomly selected from public universities in Malaysia. The analysis of the questionnaires has shown that most respondents accept negatively the use of impoliteness strategies in social media interactions. Essentially the results of the questionnaire were inconsistent with the practicalities of the interaction on Facebook, which clearly demonstrated the widely used impoliteness strategy.